LuCaP Prostate Cancer Patient‐Derived Xenografts Reflect the Molecular Heterogeneity of Advanced Disease and Serve as Models for Evaluating Cancer Therapeutics. Issue 6 (3rd February 2017) - Nguyen, Holly M.; Vessella, Robert L.; Morrissey, Colm; Brown, Lisha G.; Coleman, Ilsa M.; Higano, Celestia S.; Mostaghel, Elahe A.; Zhang, Xiaotun; True, Lawrence D.; Lam, Hung‐Ming; Roudier, Martine; Lange, Paul H.; et al.
Abstract : BACKGROUND: Metastatic prostate cancer is a common and lethal disease for which there are no therapies that produce cures or long‐term durable remissions. Clinically relevant preclinical models are needed to increase our understanding of biology of this malignancy and to evaluate new agents that might provide effective treatment. Our objective was to establish and characterize patient‐derived xenografts (PDXs) from advanced prostate cancer (PC) for investigation of biology and evaluation of new treatment modalities. METHODS: Samples of advanced PC obtained from primary prostate cancer obtained at surgery or from metastases collected at time of death were implanted into immunocompromised mice to establish PDXs. Established PDXs were propagated in vivo. Genomic, transcriptomic, and STR profiles were generated. Responses to androgen deprivation and docetaxel in vivo were characterized. RESULTS: We established multiple PDXs (LuCaP series), which represent the major genomic and phenotypic features of the disease in humans, including amplification of androgen receptor, PTEN deletion, TP53 deletion and mutation, RB1 loss, TMPRSS2‐ERG rearrangements, SPOP mutation, hypermutation due to MSH2/MSH6 genomic aberrations, and BRCA2 loss. The PDX models also exhibit variation in intra‐tumoral androgen levels. Our in vivo results show heterogeneity of response to androgen deprivation and docetaxel, standard therapies for advanced PC, similar to the responses of patients to these treatments. CONCLUSIONS: The LuCaP PDX series reflects the diverse molecular composition of human castration‐resistant PC and allows for hypothesis‐driven cause‐and‐effect studies of mechanisms underlying treatment response and resistance. Prostate 77: 654–671, 2017 . © 2017 The Authors. The Prostate Published by Wiley Periodicals, Inc.